Cumulative Causation at Work: Intergenerational Transfers and Social Capital in a Spatially Varied Economy - Andrea Gentili; Luca Ferretti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper models the dynamic of migration with a particular focus on the cumulative process that causes a variation in the distribution of income in sending communities and therefore a variation in the distribution of skills across different cohorts. The model provides a theoretical framework to Cumulative Causation theory of migration and specifically a theoretical rationale behind the use of migration prevalence ratio to study migration flows. Moreover the model shows how brain drain (in sending communities) and negative cohort effect in terms of education (in receiving communities) are the result of a positive selection of migrants in terms of skills if there is a intergenerational transmission of education.
Keywords: J15; J24; E24; 330